Pharmaceuticals: Beating the Hell Out of the Average - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2021)
A lot has been written on the imminent decline of pharmaceuticals: their falling production, reduced R&D, declining innovation, the opioid crisis, patent cliffs, biting competition from generic drugs, growing opposition to IPR. The list goes on. Judging by the yardsticks that matter the most, though – namely, the companies' relative profit and relative capitalization – pharmaceuticals are doing just fine. In fact, based on these yardsticks, they remain the most powerful corporate sector of all.
Keywords: P16; P26; 330; capitalization; finance; pharmaceutical; power; profit